Magnitude −7 level earthquakes: A new lower limit of self‐similarity in seismic scaling relationships. Issue 13 (3rd July 2014) - Yoshimitsu, Nana; Kawakata, Hironori; Takahashi, Naoki
Abstract Microfractures occurring in a rock sample that are called acoustic emission (AE) events show some similar features to earthquakes. However, it remains to be shown whether or not AE equate to ultramicroearthquakes. In this study, we show the existence of magnitude −7 level earthquakes based on seismological analyses of AE source parameters. Advances in multichannel, broadband, high‐speed continuous recording of AE under seismogenic pressure conditions has facilitated increasingly robust measurement. Source parameters of AE show that AE events satisfy the same scaling relationship as natural earthquakes in which seismic moment is inversely proportional to the cube of corner frequency. This result suggests that both millimeter scale fractures and natural earthquakes of kilometer scale ruptures are highly similar as physical processes. Hence, AE events can be interpreted as ultramicroearthquakes having a magnitude of about −7. These results demonstrate that laboratory observation is an effective approach in studying natural earthquake generation process.